Pengaruh Economic Value Added (EVA) dan Market Value Added (MVA) terhadap Harga Saham pada PT Telkom Indonesia Tbk Tahun 2012-2023 - Aas Yasnia; Hendri Prasetyo (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to determine the effect of Economic Value Added (EVA) and Market Value Added (MVA) on stock prices. The population of this research is the financial report of PT Telkom Indonesia Tbk which was taken from the official website. Based on sampling in this research, the samples used were Economic Value Added (EVA) and Market Value Added (MVA), and stock prices with a period of 12 years, namely in 2012-2023. Secondary data is in the form of the company's annual report/sustainability report. This type of research is a quantitative type that is associative in nature. The data analysis technique used is multiple linear regression analysis, classical assumption test, t test, F test, and coefficient of determination test, processed using SPSS 25. Based on the results of data analysis it can be stated that Economic Value Added (EVA) and Market Value are simultaneously Added (MVA) has an effect on share prices. Partially, it shows that Economic Value Added (EVA) has a t value of 2.238 < t table 2.228 and a significant value of 0.052 > 0.05, which means it has no influence on the share price at PT Telkom Indonesia Tbk and Market Value Added (MVA) has a t value of 8.134 > ttable 2.2248 and a significant value of 0.000 <0.05, which means it has a positive and significant influence on the share price of PT Telkom Indonesia Tbk in 2012-2023.